Molecular Mechanisms and Drug Development in Aquaporin Water Channel Diseases: Aquaporin Superfamily (Superaquaporins): Expansion of Aquaporins Restricted to Multicellular Organisms - Yoshiyuki Morishita; Yasuji Sakube; Sei Sasaki; Kenichi Ishibashi (Elsevier, 2004)
Eleven aquaporins are identified in mammals. They all have highly conserved two asparagine-proline-alanine (NPA) boxes that are important for the formation of the water permeating pore. Recently we identified two new proteins in mammals distantly related to aquaporins (AQPs) with poorly conserved NPA boxes. Similarly poorly conserved AQP-like proteins were found in several genome projects of multicellular organisms. They may be subgrouped as the AQP superfamily or superaquaporins. Their function is still unknown. AQP11 knockout mice suffer from polycystic kidneys and neonatal fatality. The identification of superaquaporins will provide new insights into the role of AQPs in organogenesis. Keywords:: aquaporin, asparagine-proline-alanine (NPA) box, knockout mice, polycystic kidney